Carpy
Registered User regular

I've asked a couple instructors at my school and they didn't really have a satisfactory answer for me. hoping someone here can clarify for me or point me in the right direction.

1st derivative of a parametric equation is dy/dx = (dy/dt)/(dx/dt) which I understand. The problem comes with the 2nd derivative.

d^2y/dx^2 = d/dx(dy/dx) = (d/dt(dy/dx))/(dx/dt)

I'm not following the path from the 2nd to the 3rd step. I can calculate the 2nd derivative, I just don't see how the formula is derived.

1st derivative of a parametric equation is dy/dx = (dy/dt)/(dx/dt) which I understand. The problem comes with the 2nd derivative.

d^2y/dx^2 = d/dx(dy/dx) = (d/dt(dy/dx))/(dx/dt)

I'm not following the path from the 2nd to the 3rd step. I can calculate the 2nd derivative, I just don't see how the formula is derived.

0

## Posts

You're basically calculating the derivative of: dydx = y'(t) / x'(t)